2011
DOI: 10.1007/s12275-011-1115-0
|View full text |Cite
|
Sign up to set email alerts
|

Responses in the expression of extracellular proteins in methicillin-resistant Staphylococcus aureus treated with rhodomyrtone

Abstract: Rhodomyrtone from a medicinal plant species, Rhodomyrtus tomentosa, is a challenged effective agent against Gram-positive bacteria, especially methicillin-resistant Staphylococcus aureus (MRSA). The present study was undertaken to provide insight into MRSA extracellular protein expression following rhodomyrtone treatment. Secreteomic approach was performed on a representative clinical MRSA isolate exposing to subinhibitory concentration rhodomyrtone (0.174 μg/ml). The identified extracellular proteins of a res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…Significant antibacterial activities of rhodomyrtone against many Gram-positive bacteria have been documented [18, 34]. Although the previous researches have attempted to explain the actions of rhodomyrtone [3537], its antibacterial mechanisms of action are still unclear. Therefore, the development of this compound as a new lead drug needs more information and researches on its modes of action.…”
Section: Discussionmentioning
confidence: 99%
“…Significant antibacterial activities of rhodomyrtone against many Gram-positive bacteria have been documented [18, 34]. Although the previous researches have attempted to explain the actions of rhodomyrtone [3537], its antibacterial mechanisms of action are still unclear. Therefore, the development of this compound as a new lead drug needs more information and researches on its modes of action.…”
Section: Discussionmentioning
confidence: 99%
“…Cho et al (2008) demonstrated that tea polyphenol can differentially induced the expression of 3 proteins in MRSA whereas Sianglum et al (2011) on the other hand, reported that out of a total of 203 spots in common between the treated and untreated protein expression profiles, 18 were present only in rhodomyrtone-treated MRSA. A study of the expression of extracellular proteins by Visutti et al (2011) revealed that the identification of 4 amino acid sequences from 21 protein spots from the rhodomyrtone-treated MRSA were predicted as signal peptides sequences. …”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Limsuwan et al (2009) reported that rhodomyrtone exhibited no bacteriolytic activity against Streptococcus mutans. In addition, proteome studies showed that rhodomyrtone at a subinhibitory concentration (0.174 mg ml 21 ) suppressed the expression of extracellular proteins of MRSA involved in cell wall hydrolysis such as staphylococcal secretory antigen (Visutthi et al, 2011). In contrast, close observation by transmission electron microscope in a parallel study on cellular proteomic analysis illustrated that some cell lysis occurred in rhodomyrtone-treated MRSA cells (Sianglum et al, 2011).…”
Section: Discussionmentioning
confidence: 99%